2016
DOI: 10.1002/pds.4074
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of the age and sex distribution of the UK Clinical Practice Research Datalink and the total Dutch population

Abstract: Results from observational studies that have used CPRD data are applicable to the Dutch population, and a useful resource for decision making in the Netherlands. Nevertheless, differences in drug exposure likelihood between countries should be kept in mind, as these could still cause variations in the actual population studied, thereby decreasing its generalizability. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Since 1987, the CPRD has recorded data such as patient demographics, medical history, laboratory test results, medical diagnosis and prescription details [13]. The CPRD has been extensively used and validated for pharmacoepidemiological and epidemiological research, and has been shown to be representative for populations outside the UK [13,14]. The protocol for this study was approved by the Independent Scientific Advisory Committee for Medicines and Healthcare products Regulatory Agency (MHRA) Database research ( protocol 18_107).…”
Section: Methodsmentioning
confidence: 99%
“…Since 1987, the CPRD has recorded data such as patient demographics, medical history, laboratory test results, medical diagnosis and prescription details [13]. The CPRD has been extensively used and validated for pharmacoepidemiological and epidemiological research, and has been shown to be representative for populations outside the UK [13,14]. The protocol for this study was approved by the Independent Scientific Advisory Committee for Medicines and Healthcare products Regulatory Agency (MHRA) Database research ( protocol 18_107).…”
Section: Methodsmentioning
confidence: 99%
“…In patients without diagnosed HF or isolated loop-diuretic use at AF diagnosis, the crude incidence of HF or new isolated loop-diuretic use was calculated from the number of new cases divided by the sum of all individual person-years in the cohort. Standardised incidence rates were computed based on the age and gender distribution of the UK population in CPRD in 2011 [ 13 ]. The Aalen-Johansen estimator was used to compute overall and gender-stratified cumulative incidence curves for diagnosed HF and isolated loop-diuretic use, and death before HF as competing risks.…”
Section: Methodsmentioning
confidence: 99%
“…A population-based cohort study was performed using the CPRD. The CPRD collates the computerized medical records of general practitioners (GPs) [17,18]. The data recorded in the CPRD include demographic information, prescription details, clinical events, preventive care provided, specialist referrals, and hospital admissions.…”
Section: Data Sourcementioning
confidence: 99%